Evaluation of the Antioxidant Activity of Three Formulations of Hair Cosmetic Products Containing the Essential Oil of Clinopodium bolivianum (Benth.) Kuntze “inca muña” - Obispo Huamani, Raymí Celeste (2025)
Clinopodium bolivianum (Benth.) Kuntze, commonly known as muña, inca muña or koa, has traditionally been used for its medicinal properties in digestive disorders. Some studies have revealed its antioxidant potential and antibacterial activity. This study determined the volatile components, evaluated the antioxidant capacity of C. bolivianum essential oil and its incorporation into three hair cosmetic formulations: shampoo, combing cream, and capillary lotion. Gas Chromatography–Mass Spectrometry (GC–MS) confirmed pulegone as the main component, accounting for 66.85% of the essential oil. The antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays, with Trolox (6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid) as a reference compound. The essential oil exhibited significant radical scavenging activity, with IC50 values of 1344.0 ± 12.23 µg/mL for DPPH and 40.125 ± 1.25 µg/mL for ABTS. Among the formulated cosmetic products, the combing cream containing 0.5% of the essential oil demonstrated the highest antioxidant activity, with IC50 values of 0.72 µg/mL (DPPH) and 0.068 µg/mL (ABTS). In contrast, the shampoo and capillary lotion showed lower antioxidant potential. The stability evaluation confirmed that all formulations maintained their physicochemical properties under accelerated conditions. These findings highlight the potential application of C. bolivianum essential oil as a natural antioxidant in cosmetic formulations, contributing to its protective and functional properties.